2020
DOI: 10.1111/ijn.12886
|View full text |Cite
|
Sign up to set email alerts
|

Ethical considerations referred to in child health research published in leading nursing journals: 2015–2019

Abstract: BackgroundChild health research comprises complex ethical considerations. Understanding the extent to which the ethical process is reported in child health research is needed to improve reporting.AimsTo identify reportage of ethical considerations in child health research in leading nursing and paediatric journals.MethodsAll child health research published between 2015 and 2019 in 10 leading nursing journals and two paediatric journals were retrieved and critically appraised for the reportage of informed conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Research with children is essential but challenging (Isaacs, 2017) -even more so when new methods push the frontiers of previous approaches to improve the inputs, outputs, and outcomes of the research process (Hughes et al, 2021). As children are limited in their freedom to make choices and ability to protect their interests (Wu et al, 2021), specific ethical frameworks that outline the provisions to be undertaken by researchers to protect the rights of participating children are critical (Strode and Slack, 2015). Such ethical frameworks should observe principles of non-discrimination, voluntariness, informed consent, and transparency.…”
Section: Practical and Ethical Considerationsmentioning
confidence: 99%
“…Research with children is essential but challenging (Isaacs, 2017) -even more so when new methods push the frontiers of previous approaches to improve the inputs, outputs, and outcomes of the research process (Hughes et al, 2021). As children are limited in their freedom to make choices and ability to protect their interests (Wu et al, 2021), specific ethical frameworks that outline the provisions to be undertaken by researchers to protect the rights of participating children are critical (Strode and Slack, 2015). Such ethical frameworks should observe principles of non-discrimination, voluntariness, informed consent, and transparency.…”
Section: Practical and Ethical Considerationsmentioning
confidence: 99%
“…Children are prone to emotional breakdowns, limb twisting, crying, and lack of cooperation during infusion, which not only hinder the work of nursing staff but also lead to accidents such as fluid extravasation and infusion set dislodgement, requiring repeated venipuncture, which in turn aggravates the childrens’ negative emotions. This makes treatment more difficult and leads to increased dissatisfaction of parents with increased complaints, which is not conducive to building a harmonious nurse-patient relationship[ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a study on ten nursing and two paediatric journals between 2015 and 2019 found that 87.9% of articles reported ethical approval, with prospective studies showing higher rates than retrospective studies. Slightly more than half of the articles reported written informed consent and child consent (assent) were reported in 6.3–29.6% of cases (Wu et al, 2021). A recent study on health and social sciences research in Sweden found a failure to report ethical approval in 6% of publications with somatic focus, 11% with non‐somatic focus, and 27% in social sciences.…”
Section: Introductionmentioning
confidence: 99%